Where Are All the Welfare Queens? Negotiating the Conditions of Wageless Life in Contemporary American Film - Petra Požgaj ([sic])
The cultural treatment of wagelessness and welfare as its potential relief serves as a potent example of how popular culture has long functioned as a site at which American society articulates and negotiates its anxieties. Observing a recent departure from the figure of the “welfare queen” as the privileged site at which anxieties related to welfare are organized, and linking this change to the neoliberal transformations of welfare in the United States introduced by the 1996 reform, this paper adopts a Foucauldian approach to the issue of government in order to set the ground for an analysis of contemporary films which negotiate the conditions of wageless life in what has often been termed a post-welfare society. Looking at Beasts of the Southern Wild and The Florida Project as illustrative of a broader representational trend, this paper examines the role of popular culture in negotiating social changes by exploring the ways in which the two films negotiate dominant discourses of personal responsibility and work opportunity through the newly emergent figure of the “surplus population.”